2010
DOI: 10.1089/dia.2009.0147
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Glucose Control: Safe and Reliable Glycemic Control Using Enhanced Model Predictive Control Algorithm in Medical Intensive Care Unit Patients

Abstract: In our single-center, noncontrolled study the eMPC algorithm was a safe and reliable method to control BG in critically medical ICU patients for the whole length of ICU stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…By contrast, SC continuous glucose monitoring (CGM) and CSII devices are smaller, less invasive, and already widely used in ambulatory diabetes care. Thus, CGM and CSII have been used in the development of an AP, and several clinical and in silico evaluations of the AP have been reported (Amrein et al, 2010; Atlas, Nimri, Miller, Grunberg, & Phillip, 2010; Breton et al, 2012; Cobelli et al, 2012; Dassau et al, 2010, 2013; Dua & Pistikopoulos, 2005; Harvey et al, 2014; Hovorka et al, 2011; Kovatchev et al, 2010; Murphy et al, 2011; Parker, Doyle, & Peppas, 1999; Patek et al, 2012; Steil, Rebrin, Darwin, Hariri, & Saad, 2006; Weinzimer et al, 2008; Zisser et al, 2012). However, substantial time delays associated with SC insulin delivery (i.e., the slow absorption peak at 50–60 min and long residence time of 6–8 h, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, SC continuous glucose monitoring (CGM) and CSII devices are smaller, less invasive, and already widely used in ambulatory diabetes care. Thus, CGM and CSII have been used in the development of an AP, and several clinical and in silico evaluations of the AP have been reported (Amrein et al, 2010; Atlas, Nimri, Miller, Grunberg, & Phillip, 2010; Breton et al, 2012; Cobelli et al, 2012; Dassau et al, 2010, 2013; Dua & Pistikopoulos, 2005; Harvey et al, 2014; Hovorka et al, 2011; Kovatchev et al, 2010; Murphy et al, 2011; Parker, Doyle, & Peppas, 1999; Patek et al, 2012; Steil, Rebrin, Darwin, Hariri, & Saad, 2006; Weinzimer et al, 2008; Zisser et al, 2012). However, substantial time delays associated with SC insulin delivery (i.e., the slow absorption peak at 50–60 min and long residence time of 6–8 h, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the hope of improving the quality of GC and reducing workload, several algorithms have been developed. The enhanced Model Predictive Control (eMPC) algorithm has been studied in several clinical trials where it was found to be efficient and safe [22-27]. It is now implemented in the CE-certified Space GlucoseControl (SGC; B. Braun, Melsungen, Germany) which was the first device on the market available for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, aggressive insulin protocols in cardiac surgery and critical care patients have been associated with considerably higher rates of hypoglycemia. 25,26 Indeed, tight glucose control goals in critical care units have resulted in unacceptably high rates of hypoglycemia 9,12 and increased mortality. 8 Anesthesiologists are especially concerned about hypoglycemia because symptoms are masked by general anesthesia.…”
Section: Discussionmentioning
confidence: 99%